Water and salt stress alleviation in wheat induced by rhizosphere bacteria with multi-functional traits - Chakraborty, U.; Chakraborty, B. N.; Chakraborty, A. P.; Dey, P. L. (International Journal of Bio-resource and Stress Management, 2023)
Twenty-seven (W1-W27), twenty-three (IP1-IP23) and nine (S1-S5, N1, N2, N3 and N4) bacterial isolates from wheat (Triticum aestivum), blady grass (Imperata cylindrica ) and Bermuda grass (Cynodon dactylon) rhizosphere which were found to be highly salt-tolerant were further tested for PGPR characteristics in vitro. Those bacterial isolates showing positive responses in vitro were identified by morphological, biochemical and 16SrDNA sequencing to be Ochrobactrum pseudogregnonense (IP8), Bacillus safensis (W10), Bacillus cereus (S4). In vivo studies on salinity using B.cereus (S4), N2 and N4 revealed that all three isolates could promote growth of wheat plants significantly in terms of increased length of leaf as well as root and shoot biomass. The isolates could also elicit antioxidant responses against salt stress in wheat, as evidenced by increased activities of anti-oxidative enzymes at different hours of treatment. B. safensis and O. pseudogregnonense which were found to be drought tolerant could promote growth in six varieties of wheat tested in terms of increase in root and shoot biomass, height of plants, yield, as well as increase in chlorophyll content. Besides, the wheat plants could withstand water stress more efficiently in presence of the bacteria as indicated by delay of appearance of wilting symptoms increases in RWC of treated water stressed plants, and elevated antioxidant responses which were evident as elevated activities of enzymes such as catalase, peroxidase, ascorbate peroxidase, superoxide dismutase and glutathione reductase as well as increased accumulation of antioxidants such as carotenoids and ascorbate. Results clearly indicate that the ability of wheat plants to withstand water stress is enhanced by application of these bacteria which also function as plant growth promoting rhizobacteria. Thus, osmo-tolerant PGPR strains could be used in field condition in order to mitigate salinity and water stress in crop plants